Implementasi VoIP pada Lab Infrastruktur menggunakan Cloud Computing berbasis Kernel Based Virtual Machine (KVM) - irfiana safitri; Erwin Gunawan; Gamaria Mandar (PRODUKTIF : Jurnal Ilmiah Pendidikan Teknologi Informasi, 2022)
VoIP service or the abbreviation of Voice Over Internet Protocol is a voice communication technology that uses the internet network. VoIP is built using Cloud Computing using Cloud Computing with KVM virtualization using Proxmox VE OS. Needs to be presented to deal with these problems. The purpose of this research is to build a VoIP server to take advantage of today's telecommunications, where the costs incurred for this technology infrastructure are much cheaper than telecommunications technology in general that is used by today's society. Where the VoIP network can minimize the waste of device resources. VoIP can increase the need for IP-based real-time services.From the VoIP analysis using the NDLC (Network Development Life Cycle) research method from the existing 6 stages, only 3 stages are used in the test, namely analysis, design and simulation. Then the Voip 2 Concurrent Call scenario will be tested. From the capture results obtained from wireshark. For scenario 2 concurrent calls, the average value of delay = 39.5 ms, the average value of jitter = 27.6 ms and the average value of packet loss = 0.00 %, while the scenario 4 concurrent calls obtained the average value of delay = 40.8 ms, the average value of jitter = 9.6 ms and the average value of packet loss = 0.00%. so the conclusion from the two scenarios is categorized as good and does not exceed the recommended ITU-T. and the results of this study for cloud computing is used for virtual purposes based on the need for cheap alternative connections.